Pengembangan Ekonomi Kreatif Usaha Kuliner - D. Made Darmawati; Nur Busyra; Ervin Azhar (TAAWUN, 2022)
The creative economy evolution in a new economic era in a new millennial digital society, which intensified the information and creativity of resources, the creative idea that emerged from human thought as the primary factor that spawned a unique, creative and innovative work that outsourced individual human thinking. The methods we use in the performance of public devotion use methods of material deepening such as arrests, and the creative economic enrichment of homemade culinary. Home-culinary and digital marketing practices, digital-based technology that offers small businesses both a novice new venture as an opportunity to provide consumers with an innovative new environment and can help improve the online digital learning process. The development of societies of home-mothers as the first start-up of a culture-based society in a systematic way that can change the economic situation of previous families for the better, the partner problem of marketing products is still conventional not to use the technology online information system. We introduced a strategy to market products through a social or educational media platform which is a website or online application that facilitates the process of buying and selling by reporting on social media. The result of this community's dedication is already generated from several already existing partners marketing strategies on Sholeha's mother, (2022) results devotion. And Mrs. Chilfi Sundari 2022 already has a certified domestic industrial food production (SP-PIRT) with numbers; 3/B.56/31.71.04.1003.01.009.R.4/3/-1.779.3/e/2020. So, the other PKK mothers are processing in creative economic development as a further training design which is the labeling or packaging of products becomes more attractive and free to trade.